Phytotherapy for the Treatment of Chronic Venous Insufficiency. The Buckeye - Sánchez de Membiela, Mª Teresa (Revista Internacional de Ciencias Podológicas, 2011)
Chronic venous insufficiency is a common disease associated with a large economic impact and a significantdeterioration in the quality of life of patients. Currently, the standard treatment are compression stockings, however this often causes discomfort and a low adhesion to the treatment so other therapies should be considered. Nowadays, various synthetic drugs for the treatment of chronic venous insufficiency are available. However, due to increasing demand from patients for phythoterapy treatments and the high use that has been done in Europe of horse chestnut for treating this condition, it was considered important to provide a brief review of the main current pharmacotherapeutic aspects of the of horse chestnut seeds extract, which compound responsible for the pharmacological activity is the mixture of triterpene saponins known as aescin or escin.